(untitled) (Indian Journal of Veterinary Pathology, 2025)
A case of ovarian papillary adenocarcinoma in a Spitz was reported. Twelve years old female spitz dog was presented to the Veterinary Clinical Complex, Veterinary College and Research Institute, Namakkal with the history of progressive abdominal distension for the past one month. Haematology and serum biochemistry revealed leucocytosis and mild hypercalcemia respectively. Lateral abdominal radiography and transabdominal ultrasonography showed homogenous intra-abdominal mass and irregular mass adjacent to spleen respectively. The computed tomography of abdomen exhibited presence of mass beneath both kidneys extending up to bladder with HU index 60 to 75 suggestive of tumor. The exploratory laparotomy revealed large cauliflower like mass in right ovary and was removed surgically by ovariohysterectomy. The impression smears from the mass showed clusters of cells with indistinct cell border and significant anisokaryosis. Histopathologically, glandular cells were arranged in papillary pattern with irregular branches and the neoplastic cells showed cellular atypia, scanty eosinophilic cytoplasm with hyperchromatic ovoid nuclei. Furthermore, the immunohistochemistry showed moderate to strong expression for pan-cytokeratin and estrogen receptor (ER). Based on histopathology and immunohistochemistry the tumor was confirmed as ovarian papillary adenocarcinoma.